The Relationship Between Emotional Schemas and Co-Rumination Among University Students (Journal of the College of Basic Education, 2026)
This study aimed to explore the relationship between emotional schemas and co-rumination among university students. Emotional schemas refer to the cognitive-affective structures individuals use to evaluate and respond to emotional experiences, while co-rumination refers to the excessive discussion of personal problems within close relationships. A sample of 250 students was selected using convenience sampling from four Iraqi universities. Data were collected via electronic questionnaires, including an adopted Emotional Schemas Scale and Co-Rumination Scale, both validated for reliability and validity. Results showed high levels of both emotional schemas and co-rumination among students. A significant positive correlation (r = 0.80) was found between emotional schemas and co-rumination; students with negative beliefs about their emotions were more likely to engage in frequent, emotionally intense conversations with peers. Regression analysis indicated that emotional schemas accounted for about 64% of the variance in co-rumination, emphasizing their central role in shaping interpersonal emotion regulation strategies. Additionally, gender differences were found in emotional schemas favoring males, while no significant gender differences appeared in co-rumination. These findings align with Leahy’s theoretical framework (2002) and Rose’s model of co-rumination (2002), suggesting that maladaptive emotional-cognitive beliefs, when reflected in interpersonal coping behaviors, may heighten emotional distress. The study highlights the importance of interventions aimed at restructuring emotional schemas, particularly within university settings, to reduce reliance on maladaptive strategies like co-rumination and enhance healthy emotional processing.